Trade‐offs of forest management scenarios on forest carbon exchange and threatened and endangered species habitat. Issue 10 (27th October 2021) - McDowell, Nate G.; Tan, Zeli; Hurteau, Matthew D.; Prasad, Rajiv
Abstract: Management of forest lands under climate warming poses challenges to managers, some of which are difficult to predict. Examining the trade‐offs associated with forest stewardship choices is essential to avoid consequences associated with loss of natural capital. We utilized LANDIS‐II process model simulations for three forested sites located in disparate parts of the United States with the purpose of understanding the trade‐offs imposed by management choices under climate warming and associated wildfire. There were only small trade‐offs that emerged from the simulations, between habitat area for threatened and endangered species (TES), net ecosystem exchange for CO2 (NEE), and risk of wildfire. Stand management in the form of thinning and prescribed burning typically increased NEE while simultaneously increasing habitat for TES, while reducing the risk of wildfire. These benefits were also observed under a climate warming scenario; however, the benefits were greatly outweighed by the negative impacts of warming on both TES habitat and NEE. Balancing these ecosystem services via thinning and burning treatments is a strategic approach to mitigate risks of wildfire both currently and under a warming future climate.